Formulating Methyl Salicylate Microemulsion - Thi Hai Yen, Tran; Thuc Oanh, Hoang; Thi Thu Giang, Vu (VNU Journal of Science: Medical and Pharmaceutical Sciences, 2020)
Methyl salicylate (MS) is an active pharmaceutical ingredient of NSAIDS group, often used in topical dosage forms such as ointments, gels, patches, etc. to treat and relieve muscle and joint diseases. Microemulsion is a potential drug delivery system thanks to its various advantages: oil droplet size of only several nanometres, good appearance, transparence, simple methods of preparation and simple application in manufacturing. This study aims to formulate a phase diagram to identify the area of ​​methylsalicylate microemulsion formation and formulate MS microemulsion 1% and 5%. The water titration method was used to build the phase diagram. MS microemulsions were evaluated for their appearance, thermodynamic stability, particle size and stability after storage. The study results show that the using of isopropyl mirystate as the oil phase, Tween 80 as a surfactant and Transcutol P auxiliary surfactant resulted in a larger microemulsion formation area than the using of coconut oil as the oil phase and polyethylene glycol 200 as an auxiliary surfactant. MS microemulsion 5% and 1% had a droplet size of about 20 nm and thermodynamical stability. As MS microemulsion 5% was stable by particle size, its change was not statistically significant after a three-week storage. Keywords Methyl salicylate, microemulsion, phase diagram. References [1] H.O. Lawal, G.O. Adewuyi, A.B. Fawehinmi, A.O. Adeogun, S.O. Etatuvie, Bioassay of herbal mosquito repellent formulated from the essential oil of plants, Journal of Natural Products. 5 (2012) 109-115. http://journalofnaturalproducts.com/Volume5/15_Res_paper-14.pdf. [2] New York State Integrated Pest Management Program, Lemongrass oil profile active ingredient eligible for minimum risk pesticide use. https://ecommons.cornell.edu/bitstream/handle/1813/56130/lemongrass-oil-MRP-NYSIPM.pdf, 2019 (accessed 5 November 2019). [3] Organisation for Economic Co-operation and Development, Citral CAS N°:5392-40-5. https://hpvchemicals.oecd.org/UI/handler.axd?id=0ea83202-3f4f-4355-be4f-27ff02e19cb9, 2001 (accessed 5 November 2019). [4] R. Arun, K.C.K. Ashok, V.V.N.S.S. Sravanthi, Cyclodextrins as drug carrier molecule: a review, Scientia Pharmaceutica 76 (2008) 567-598. http://dx.doi.org/10.3797/scipharm.0808-05. [5] O.I. Adeniran, E. Fabiyi, A cream formulation of an effective mosquito repellent: a topical product from lemongrass oil (Cymbopogon citratus) Stapf, Journal of Natural Product and Plant Resources, 2 (2012) 322-327. https://pdfs.semanticscholar.org/13bf/993de8f77462335ebc07365adb38e56e706f.pdf. [6] P. Borman, D. Elder, Q2(R1) Validation of analytical procedures: text and methodology, in: A. Teasdale, D. Elder, R.W. Nims (Eds), ICH quality guidelines: an implementation guide, John Wiley & Sons Inc., Hoboken, 2018, pp. 127-166. [7] S. Agrawal, N. Haldankar, A. Jadhav, Formulation of natural mosquito repellent, International Journal of Advance Research, Ideas and Innovations in Technology 4 (2018) 11-17. https://www.ijariit.com/manuscripts/v4i1/V4I1-1143.pdf. [8] Vietnamese pharmacopoeia commission, Vietnamese pharmacopoeia V part 2, Medical Publishing House Co., Ltd, Ha Noi, 2018 (in Vietnamese). [9] M.A.B. Edris, A.S.Y. Mamat, M.S. Aslam, M.S. Ahmad, Insect repellent properties of Melaleuca alternifolia, Recent Advances in Biology and Medicine 2 (2016) 57-61. http://dx.doi.org/10.18639/RABM.2016.02.293742. [10] R. Gaonkara, S. Yallappab, B.L. Dhananjayac, G. Hegde, Development and validation of reverse phase high performance liquidchromatography for citral analysis from essential oils, Journal of Chromatography B. 1036 (2016) 50–56. http://dx.doi.org/10.1016/j.jchromb.2016.10.001. [11] D. Miron, F. Battisti, C.S.T. Caten, P. Mayorga, E.E.S. Schapoval, Spectrophotometric simultaneous determination of citral isomers in cyclodextrin complexes with partial least squares supported approach, Current Pharmaceutical Analysis 8 (2012) 401-408. http://dx.doi.org/10.2174/157341212803341735. [12] L. Huber, Validation and qualification in analytical laboratories, Informa Healthcare USA Inc., New York, 2007. [13] N.D. Wilson, M.S. Ivanova, R.A. Watt, A.C. Moffat, The quantification of citral in lemongrass and lemon oils by near‐infrared spectroscopy, Journal of Pharmacy and Pharmacology 54 (2002) 1257-1263. http://dx.doi.org/10.1211/002235702320402107. [14] N. Dudai, O. Larkov, E. Lewinsohn, Simple colorimetric measurement of citral in lemon scented essential oils using Schiff’s reagent, Future for Medicinal and Aromatic Plants, 26 (2004) 499-504. http://dx.doi.org/10.17660/ActaHortic.2004.629.64.